BACK ANALYSIS INVESTIGATION OF THE FACTORS CONTRIBUTING TO SETTLEMENT IN EMBANKMENTS ON SOFT SOIL - Pratama, Andreas Raya; Al Hanif, Basit; Soerjatmodjo, Irnanda Satya (International Journal of Civil Engineering and Infrastructure, 2024)
The economic growth of a region is intricately linked to infrastructure development, especially toll highways, which augment the efficiency of products and services distribution, diminish logistical expenses, and promote access to economic hubs. The construction of toll roads, particularly embankments on soft soil foundations, encounters considerable obstacles due to the limited bearing capacity and high compressibility of soft soil, resulting in settlement issues that may threaten structural integrity and functionality. This research examines settlement behavior in embankments on soft soil by a "Back Analysis" methodology, comparing actual field settlement data with predictive modeling outcomes derived from the finite element method (FEM). Field data and FEM simulations were evaluated to determine the precision of predictive models and their capacity to represent the intricate stress-strain behavior of soft soil. The findings underscore the necessity of combining field validation with sophisticated modeling tools to enhance predictive accuracy and guide effective construction and ground improvement methodologies. This study offers significant insights for engineers and politicians to guarantee the enduring performance and sustainability of toll road infrastructure.